2001
DOI: 10.7326/0003-4819-135-3-200108070-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two Different Dosages of Intravenous Immunoglobulin on the Incidence of Recurrent Infections in Patients with Primary Hypogammaglobulinemia

Abstract: In patients with hypogammaglobulinemia, doubling the standard dose of intravenous immunoglobulin significantly reduced the number and duration of infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
111
3
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(138 citation statements)
references
References 17 publications
13
111
3
9
Order By: Relevance
“…The prescribed doses, calculated with the number of grams of Ig ordered, the patient's weight, and the frequency of administration, were generally in accordance with the recommended dose of 400 to 600 mg/kg/month [8,[14][15][16][17]. The most common frequency of IV Ig dosing was every 4 weeks, consistent with the survey by Yong et al, which reported that 87 % of surveyed allergist/immunologists initially prescribed this frequency [18].…”
Section: Discussionsupporting
confidence: 69%
“…The prescribed doses, calculated with the number of grams of Ig ordered, the patient's weight, and the frequency of administration, were generally in accordance with the recommended dose of 400 to 600 mg/kg/month [8,[14][15][16][17]. The most common frequency of IV Ig dosing was every 4 weeks, consistent with the survey by Yong et al, which reported that 87 % of surveyed allergist/immunologists initially prescribed this frequency [18].…”
Section: Discussionsupporting
confidence: 69%
“…Patients require immunoglobulin replacement therapy, which can be administered intravenously (IVIG) or subcutaneously (SCIG) [7][8][9][10][11][12][13][14]. Subcutaneous administration produces stable serum IgG levels and is associated with fewer systemic adverse events (AEs).…”
Section: Introductionmentioning
confidence: 99%
“…bulin therapy (adults, 600 mg/kg of body weight every 4 weeks) significantly reduces the number and duration of infections as compared with the standard immunoglobulin dose (adults, 300 mg/kg of body weight every 4 weeks) (7). The amount of immunoglobulin supplementation should be increased for cases with recurrent bacterial infections.…”
Section: Discussionmentioning
confidence: 99%